Manajemen Laba: Sebuah Studi Literatur - Angel Manuela; Ariska Berlian Nur Wulan; Leny Septiani; Carmel Meiden (Universitas Warmadewa, 2022)
Earnings management is one of the most commonly done practices in accounting. As early as 1989 this topic has been discussed, and is still being studied to date. The discussion on earnings management varies, one of which is about the factors that may affect earnings management, such as audit quality, good corporate governance (GCG), profitability, company size, leverage, financial distress, effectiveness of the board of commissioners and effectiveness of audit committee, debt policy, ownership structure, and corporate social responsibility (CSR). Since earnings management can decrease the quality of financial information, it is crucial to identify the factors that influence this practice so that they can be given more attention and as a result earnings management can be diminished. This study was conducted by reviewing 21 previous studies related to earnings management and concluding the findings of these studies. Articles reviewed are from within and outside Indonesia with publication time span of 2017-2021. For domestic articles, those with Science and Technology Index (Sinta) are chosen, while the international articles used are those indexed by Scopus and/or Google Scholar. From this literature study, it is concluded that the factors influencing earnings management practices are ownership structure (managerial and institutional ownership), firm size, firm age, leverage, profitability, sales growth, firm performance, effectiveness of board of commissioners and audit committee, audit quality, debt policy, tax planning, CSR, operational cash flow, free cash flow, board of directors characteristics (gender diversity,independence, and CEO duality), GCG, debt financing, corporate strategy, and cash holding.